Study on underlying habits of children seeking orthodontic treatment from Dental Institute, Colombo. - Usgodaarachchi, U.S (My University, 1995)
The commonest habit seen was thumb sucking,and the second commonest was nail biting.Lip biting,finger sucking and dummy sucking habits were also common amongst the children examined,with decreasing order of prevalence.Common malocclusions seen amongst children with sucking habits were characterized by increased overjet,reduced overbite,anterior openbite,spacing in upper anterior arch and crowding of lower anterior arch, whereas in children with biting habits malocclusions such as raised overjet,crowding and crossbites of anoterior dental arches and varying degrees of overbite were common.